The Third World and decision making in the International Monetary Fund : the quest for full and effective participation - Ferguson, Tyrone; Graduate Institute of International Studies (Geneva, Switzerland) (London ; New York : Pinter Publishers, 1988)
This book sets out the grounds for discontent evinced by the Third World with the decision-making rules of the IMF. It shows how the Third World has sought both further participation and more effective influence over substantive fund policies and programmes.
"A publication of the Graduate Institute of International Studies, Geneva."
Includes index.
Includes bibliographical references : p. [241]-257.
osc 01/12/16
Loans
Keywords: Decision making; International Monetary Fund; Management; Third world; Developing countries